Strategi Pengembangan Pariwisata Berbasis Kearifan Lokal Studi Kasus Pelestarian Kothek Lesung di Desa Wisata Sambongrejo - Nabiran Fangki Bawono (Universitas Sebelas Maret (UNS), 2025)
Utilization of local wisdom such as art attractions has great potential to increase tourist attractions by providing tourists with a unique and memorable tourism experience, so this must be done with full consideration. This study aims to determine the strategy for developing a tourist village by utilizing the local wisdom of Kothek Lesung. Another objective of this study is to determine the impact of preserving local wisdom on the economic and social sectors of society. Kothek Lesung has undergone a change in function from a rice pounding tool to a traditional musical instrument. This study uses Structuration Theory to examine the role of the community as an agent in the preserving local wisdom to develop tourist villages. The three concepts in structuration theory, namely significance, domination, and legitimacy, are used to examine the role of agents in utilising Kothek Lesung as a domination structure. This study uses a qualitative case study research method with data collection techniques through observation, interviews, and documentation. The results of this study show that local wisdom can be an invaluable asset for the development of tourism villages, as evidenced by the preservation of the Kothek Lesung in the tourism village of Kampung Samin Sambongrejo. The existence of a tourism village has been shown to result in the creation of new economic opportunities, including homestay management, MSMEs, and cultural attractions. These opportunities have the potential to enhance community welfare while respecting the community's primary role as farmers. The preservation of Kothek Lesung reflects Sedulur Sikep's social values, including togetherness, solidarity, and respect for local culture. This, in turn, serves to strengthen the village's identity as a unique and authentic cultural tourism destination